Australian thraustochytrids: Potential production of dietary long-chain omega-3 oils using crude glycerol. (December 2015) - Lee Chang, Kim Jye; Paul, Helen; Nichols, Peter D.; Koutoulis, Anthony; Blackburn, Susan I.
Abstract: Thraustochytrids can produce high amounts of docosahexaenoic acid (DHA, 22:6ω3). Glycerol, a by-product of biodiesel production from vegetable oil and animal fats, is becoming increasingly available. We investigated the potential of Australian thraustochytrids to use crude glycerol as the main carbon source for production of long-chain (LC, ≥C20 ) omega 3-oils. Crude glycerol content was analysed, and the growth kinetics of eight thraustochytrid strains was examined with crude glycerol. Aurantiochytrium sp. strains achieved higher biomass (20 g/L dry cell weight; DCW) and lipid yield (389 mg/g total fatty acids; TFA) compared to Schizochytrium, Thraustochytrium and Ulkenia spp. Impurities in the crude glycerol hindered growth of thraustochytrids, with maximum yield of 9 g/L DCW and 48% DHA TFA at 4-days. Our research shows the potential of heterotrophic thraustochytrids to provide the growing global population with a secure, environmentally sustainable alternative source of health-benefitting LC omega-3 oils for use in feeds and foods.